Anionic carbonate activation of layered (α+β) nickel hydroxide - Kovalenko, Vadym; Kotok, Valerii (Eastern-European Journal of Enterprise Technologies, 2019)
Nickel hydroxide is widely used as the active material in supercapacitors. Samples of Ni(OH)2 with the (α+β) layered structure, synthesized in the slit-diaphragm electrolyzer, are the most active. The possibility of carbonate activation of layered (α+β) Ni(OH)2 was studied by the synthesis of samples in the slit-diaphragm electrolyzer using a mixture of sodium hydroxide and sodium carbonate as the electrolyte. The molar part of sodium carbonate in the NaOH+Na2CO3 mixture was controlled by acid titration in the presence of two indicators. The synthesis of nickel hydroxide samples was conducted at the molar part of carbonate from 0.16 (NaOH without the additional introduction of carbonate) to 0.83. The crystal structure of the samples was studied by means of X-ray diffraction analysis, electrochemical characteristic – by means of cyclic voltammetry and galvanostatic charge-discharge cycling in the accumulator regime. By means of XRD analysis, it was found that upon increasing the molar part of carbonate in the anolyte to 0.49, the crystallinity of the monophase layered (α+β) structure increases. It was found that a further increase of the carbonate part results in a more amorphous structure due to a partial breakdown of the hydroxide lattice with the formation of basic salts and formation of the bi-phase system. This conclusion is supported by cyclic voltammetry and discharge curves. The study of the electrochemical characteristics revealed, that for the molar part of carbonate below 0.39, carbonate activation of hydroxide occurs resulting in an improved specific capacity. Increasing the carbonate part to 0.49 results in a lower specific capacity, and even further increase results in the breakdown of hydroxide into basic salts and a significant drop in electrochemical activity. Thus, it was found, that to achieve the maximum activating effect, the optimal molar part of sodium carbonate (in a mixture with sodium hydroxide) should be about 40 %. The specific capacity of nickel hydroxide under this optimal condition is 234 mA·h/g, and this sample is found to be susceptible to activation with cobalt compounds, which further improved capacity to 254 mA·h/g.